(untitled) (Economics and region, 2019)
The theoretical and methodological principles of the formation of Internet technologies in brand management are investigated. The main functions and features of the brand are identified. The place of the brand in the structure of marketing strategy is considered. Types of brand communication strategies are analyzed. The mechanism of brand management in the marketing activity of enterprises is investigated, in particular the application of modern marketing concepts in brand-oriented management. The influence of factors on the effectiveness of the brand of the company is determined. The main stages of the process of forming the brand of the company "Ai Agency" are characterized. Marketing Internet technologies of “Ai Travel Agency” LLC as a brand management tool are analyzed. There provided marketing technologies to promote their own brand.